Novel amplitude compensation for digital signal processing system using minimum phase filter - Praesomboon, Sukanya; Dejhan, Kobchai; Yimman, Surapun; Phromlikhit, Chanchai (My University, 2011)
This paper proposes minimum phase filter design and applications. The property of a minimum phase filter is having the poles and zeros inside the unit circle. The initial step is to design a minimum phase filter to obtain the specified analog of the reconstruction low pass filter, convert to digital filter using the approximate of derivative and inverse system and next the system of minimum phase filter could be implemented by output function software of digital signal processing system. The experimental result of this proposed method can also be used to compensate for attenuation of the output amplitude obtained from the reconstruction filter at high frequency of digital signal processing system. © 2011 IEEE.
Keywords: Approximate Derivative; Digital Filter; Minimum Phase Filter